Hubungan Aktivitas Fisik Selama Pembelajaran Daring dengan Tingkat Kebugaran Jasmani Mahasiswa Keperawatan - Kusuma Dewi, Ratih; Rohmah, Astika Nur (STIKES Ngesti Waluyo, 2023)
Working from home, studying from home and lockdown were the government's efforts to reduce the spread of COVID-19. Students are part of the community who experience the impact of online learning. The majority of people's physical activity during the COVID-19 pandemic in several countries is declining which affects the level of physical fitness. Good physical fitness is needed by students to carry out daily activities, one of which is learning activities. The research objective was to determine the relationship between physical activity during online learning and the level of physical fitness in students. This research is a correlative descriptive study to determine the relationship between physical activity and physical fitness, using a quantitative approach with a cross sectional design. Data were obtained from 60 respondents. Their daily physical activity was then assessed, and the Harvard Step Up Test was used to determine their level of physical fitness. Furthermore, the data were analyzed using the Spearman's rho test. After the analysis was carried out, the results obtained were p = 0.000 (<α 0.05), so that it was statistically significant. The conclusion from this study is that there is a relationship between the physical activity during online learning and the level of physical fitness of students. Most students have light physical activity due to national activity restrictions during the COVID-19 pandemic. This has an impact on students' physical fitness after online learning from home.